2023
DOI: 10.1002/inf2.12396
|View full text |Cite
|
Sign up to set email alerts
|

Intermediate phase assisted sequential deposition of reverse‐graded quasi‐2D alternating cation perovskites for MA‐free perovskite solar cells

Abstract: One‐step deposition approaches have been widely applied and developed in the fabrication of quasi‐2D perovskites. However, the regulation of quantum wells (QWs) and crystalline orientation is difficult and complicated when using this methodology. Sequential deposition is another widespread synthetic approach for preparing perovskite films and perovskite dimension engineering. In this article, δ‐CsPbI3 intermediate phase assisted sequential (IPAS) deposition is successfully carried out to fabricate MA‐free quas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…S3a-c. Thus, fewer organic dielectric layers are spanned in the out-plane direction [ 32 ], which predicts a convenient carrier transport pathway. The X-ray diffraction (XRD) patterns displayed in Figs.…”
Section: Resultsmentioning
confidence: 99%
“…S3a-c. Thus, fewer organic dielectric layers are spanned in the out-plane direction [ 32 ], which predicts a convenient carrier transport pathway. The X-ray diffraction (XRD) patterns displayed in Figs.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, fewer organic dielectric layers are spanned in the out-plane direction. [28] To get a better view of the perovskite's surface, we used atomic force microscopy (AFM) analysis. After applying a 2D layer, we observed that the surface roughness of the RA sample decreased from 39.5 to 27.3 nm (Figure 2b,f ).…”
Section: Resultsmentioning
confidence: 99%
“…Such unique features enhance the mechanical strength and improve the dimensional stability of the materials; However, initiating a self-healing process often requires substantial amounts of time and energy. These limitations can be particularly challenging for perovskite materials with fragile crystal stabilities, [90,91] complicating the application of selfhealing techniques to PSCs. Certain characteristics are crucial when considering the device applications of perovskites.…”
Section: Self-healing Polymeric Additives Via Chemical Bondingmentioning
confidence: 99%